Gender perspectives in the use of transport means and the perception of urban mobility conditions - Sousa, Isabel Cristina Nunes de [UNESP]; Peres, Renata Bovo (Univ Buenos Aires, Inst Geografia, 2023)
In this study, we sought to broaden the understanding of gender roles in the perceptions about the use of transport means and urban mobility conditions. We aimed to unders-tand better the social conditions that directly interfere with the population's displace-ment patterns and indirectly permeate the strategies and public policies designed to guide the choice of transport modes. Through the analysis of questionnaire responses, the evaluation focused on urban mobility from a gender perspective, specifically on the roles and inherent social relations. Primary data collected were statistically analyzed (descriptive and inferential analysis) to measure the influence of gender on a) use of transport means in daily commuting and b) perceptions about urban mobility con-ditions. The research occurred in a mid-sized Brazilian city in the interior of the Sao Paulo State (Sao Carlos). We found a probable relationship between the gender of the respondents and the use of the leading transport means, given the differences between men and women. However, we do not observe any influence on the perceptions of the urban mobility conditions in the studied municipality.
Keywords: Urban mobility; Gender; Perception; Public policies; Transport means